Pescadoras e pescadores artesanais em São Francisco do Sul -SC: cenários e perspectivas - Wagner, Daniela Feyh (2024)
An important activity for the populations along the Brazilian coast, artisanal fishing is a fundamental element for various fishing communities, composed of women and men from São Francisco do Sul, a municipality located on the northern coast of Santa Catarina. It is through their work in fishing that their way of life is established, partly governed by the rhythms of nature, the pace of capitalism, as well as by their own rhythm. They practice geography in their daily lives, establishing relationships with the environment in which they live, an environment marked by various inequalities, insufficient laws, lack of investment, and threats to their livelihood, such as overfishing, pollution, the advance of urbanization, and port projects, in addition to the marginalization of women. Thus, through the methodology employed in this research, the subjects involved in artisanal fishing in São Francisco do Sul, as well as their geographical context, will be presented. By utilizing theoretical frameworks, statistical data, systematic field observations, and interviews, the profile of these women and men was outlined, including their unique knowledge and practices, as well as their main challenges and perspectives.